Nation builder : John Quincy Adams and the grand strategy of the republic - Edel, Charles N., 1979- (Harvard University Press, 2014)
America's rise from revolutionary colonies to a world power is often treated as inevitable. But Charles N. Edel's provocative biography of John Q. Adams argues that he served as the central architect of a grand strategy whose ideas and policies made him a critical link between the founding generation and the Civil War-era nation of Lincoln.